Factors affecting going concern audit opinion with company size as a moderating variable in sub sector manufacturing companies registered food and beverages on the indonesia stock exchange Period 2015-2019 - rizka Hilda Siregar; Erlina Rusli; Rina Bukit (Institute of Computer Science (IOCS), 2021)
This study aims to examine and analyze the Factors Affecting Audit Opinions Going Concern With Company Size as a Moderating Variable in Manufacturing Companies on the Indonesia Stock Exchange for the 2015-2019 Period. The population in this study were 53 Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange for the 2015- 2019 period with the Census sampling method, so that the number of samples in this study was 37 companies x 5 years = 185 data observations. The data analysis method used is descriptive statistical test, logistic regression analysis and moderation regression analysis with statistical data processing software tools, namely Eviews. The results of the Wald test show that partially liquidity and leverage have a positive and significant effect on going-concern audit opinion. While profitability and sales growth partially have a negative but not significant effect on going concern audit opinion. the size of the company is not significant interaction in moderating the effect of profitability, liquidity, leverage and sales growth on going concern audit opinion on the Food and Beverage Sub Sector Manufacturing companies for the 2015-2019 period.